Scube3 is expressed in multiple tissues during development but is dispensable for embryonic survival in the mouse. - Guilherme M Xavier; Leonidas Panousopoulos; Martyn T Cobourne (PLoS ONE, 2013)
The vertebrate Scube family consists of three independent members Scube1-3; which encode secreted cell surface-associated membrane glycoproteins that share a domain organization of at least five recognizable motifs and the ability to both homo- and heterodimerize. There is recent biochemical evidence to suggest that Scube2 is directly involved in Hedgehog signaling, acting co-operatively with Dispatched to mediate the release in soluble form of cholesterol and palmitate-modified Hedgehog ligand during long-range activity. Indeed, in the zebrafish myotome, all three Scube proteins can subtly promote Hedgehog signal transduction in a non-cell autonomous manner. In order to further investigate the role of Scube genes during development, we have generated mice with targeted inactivation of Scube3. Despite a dynamic developmental expression pattern, with transcripts present in neuroectoderm, endoderm and endochondral tissues, particularly within the craniofacial region; an absence of Scube3 function results in no overt embryonic phenotype in the mouse. Mutant mice are born at expected Mendelian ratios, are both viable and fertile, and seemingly retain normal Hedgehog signaling activity in craniofacial tissues. These findings suggest that in the mouse, Scube3 is dispensable for normal development; however, they do not exclude the possibility of a co-operative role for Scube3 with other Scube members during embryogenesis or a potential role in adult tissue homeostasis over the long-term.